Fibroblas: Struktur dan Peranannya dalam Penyembuhan Luka - Erma Mexcorry Sumbayak (Fakultas Kedokteran Universitas Kristen Krida Wacana, 2015)
AbstrakSel fibroblas merupakan sel yang paling umum ditemui pada jaringan ikat dan mensintesis beberapa komponen matriks ekstraseluler (kolagen, elastin, retikuler), beberapa makromolekul anionik (glikosaminoglikans, proteoglikans). Luka merupakan keadaan rusaknya jaringan tubuh. Setelah terbentuk luka, akan terjadi proses yang sangat kompleks. Proses tersebut terdiri dari fase homeostasis dan inflamasi, proliferasi dan maturasi. Proses penyembuhan luka sangat dipengaruhi oleh peranan migrasi dan proliferasi fibroblas pada area perlukaan. Proliferasi dari fibroblas menentukan hasil akhir dari penyembuhan luka. Fibroblas akan menghasilkan kolagen yang akan menautkan luka, dan fibroblas juga akan mempengaruhi proses reepitelisasi yang akan menutup luka. Kata kunci: luka, fibroblas, kolagen AbstractFibroblasts are the most common cells found in connective tissue and synthesize some extracellular matrix components (collagen, elastin , reticular), some anionic macromolecules (glicosaminoglican, proteoglicans). Injury is a state of body tissue damage. Once injured, the healing will be a very complex process . The process consists of phases homeostasis and inflammation , proliferation and maturation. The process of wound healing is influenced by the role of migration and proliferation of fibroblasts in the area of injury. Proliferation of fibroblasts determine the final outcome of wound healing . Fibroblasts will produce collagen, which will link the wound , and fibroblasts also affects reepitilization process which would cover the wound . Key words : injury, fibroblast, collagen language:IN'> many factors such as caffeine pharmacology effects, genetic predisposition, caffeine-withdrawal symptoms, age, and social norms. The increasing the number of coffee shops in Indonesia increase the chance of people to be caffeine addict. Hence, socialization on preventing caffeine addiction, management of caffeine addiction, and psychotherapy should be given. Key words: caffeine, caffeine addiction, caffeine intoxication